MANAJEMEN PROYEK INFORMATIKA “PERANCANGAN APLIKASI CAT LOVERS BERBASIS ANDROID - Agung Wijoyo; Deni Pratama Setia Budi; Dwi Noor Saputra; Muhamad Febriyanto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Cat Lovers is a shop that usually sells pet needs such as cat food and pet equipment such as cages, fish food and vitamins, and the like. The ordering process for purchasing products is still manual offline, where purchase records and stock records still use paper and often pile up and take up a lot of space. Apart from that, product availability cannot be checked in real time by customers, so customers have to ask the seller via telephone, and for services in the form of dog walking or animal accommodation it is also not possible to confirm remotely, customers have to go to a paint shop and can had to wait because orders were full. Therefore, the aim of this project is to know and understand how the business processes carried out by Toko Cat Lovers work, identify and analyze the system that will be created in the application later, create a web application design that suits Toko Cat Lovers' needs. In working on this project we used research methods in the general project management cycle. It is hoped that the results of this project will make it easier for Cat Lovers shop customers to purchase the necessities for their pets. That way, the Cat Lovers shop owner will get more turnover.